2019
DOI: 10.1021/acsanm.9b01351
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose-Based Nanoporous Filter Paper for Virus Removal Filtration of Human Intravenous Immunoglobulin

Abstract: Human intravenous immunoglobulin (IVIG) is a highly valuable plasma-derived biotherapeutic with several important clinical indications in primary and acquired immunodeficiencies as well as autoimmune diseases, especially neuropathies. Ensuring the viral safety of plasma-derived products, such as human IVIG, is mandatory. Viral filtration is commonly used to affect viral removal in the manufacture of plasma products. Viral filtration of large volumes of a IVIG feed solution can take significant time, the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…For brevity, the detailed procedures for filter-making and characterization can be found in previous publications from our group in open access sources. 24 , 25 , 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For brevity, the detailed procedures for filter-making and characterization can be found in previous publications from our group in open access sources. 24 , 25 , 27 …”
Section: Methodsmentioning
confidence: 99%
“…For brevity, the detailed procedures for listed proteomic characterizations can be found in previous publications from our group in open access sources. 24 , 25 , 27 Additionally, for the determination of levels of specific protein biomarkers, i.e. LC3B and β-actin, Western blotting was performed with immunoblotting antiobodies.…”
Section: Methodsmentioning
confidence: 99%
“…Size-exclusion-based virus filtration is an established, reliable and robust method to physically remove all types of infective microorganisms, including viruses. 64 According to Kosiol et al (2019), 65 size-exclusion-based virus filtration has a complex internal pore network, which is capable of transmitting molecules that are smaller than 15 nm on a quantitative basis. Therefore, at least 99.99% of the larger microorganisms, including viruses (or the majority of relevant virus species), should be retained, mainly by size exclusion.…”
Section: Nanocellulose As An Antimicrobial Materials For Virusesmentioning
confidence: 99%
“…The filter paper was previously validated in numerous studies to remove several large and small-size model viruses, including retroviruses (xMuLV, 100 nm) [35], parvoviruses (MVM, 20 nm) [32,36], and model phages (ΦX174, 28 nm) [37][38][39]. Recently, it was shown that this nanocellulose-based virus removal filter paper is useful for bioprocessing human plasma-derived IgG [40].…”
Section: Introductionmentioning
confidence: 99%